According to the Law on Human Beauty (in Commemoration of E. Chervinskiene) - Beržaitė, Dagnė (Literatūra, 2020)
This paper analyzes the book of memoirs The Power of Weak written by Elena Chervinskiene, Professor of the Department of Russian Literature at Vilnius University. Chervinskiene’s book discusses her experiences being deported to the Altai region and Yakutia, part of the wave of deportations from Lithuania that began in the fateful year of 1941. The early traumatic experience determined not only the author’s further personal life but also her professional choice. It is stated that the chosen field of scientific and creative interests of the expert on classical Russian literature, author of books and articles about L. Tolstoy, F. Dostoevsky and A. Chekhov, was also shaped by the all of the human experience gained during this tragic stage of her life.
Keywords: Chervinckiene; trauma; exile; human being; profession; Russian literature